The Effect of Price and Service Quality on Customer Satisfaction of Lion Air Padang Flight Service Users - Afrida, Afrida; Mayvira, Mayvira (ADPEBI, 2024)
This study aims to find out how the influence of price variables and service quality on customersatisfaction of Lion Air Padang flight service users. The type of data used in this study is using uantitative data in the form of questionnaires from Lion Air (Padang-Jakarta) customers. The sample used in this study was Lion Air customers with the route (Padang-Jakarta) as many as 106 respondents.The results of the t-test show that price and service quality have a positive effect on customer satisfaction with a t-value calculated for the price of 4.465 with (sig 0.000<0.05), Service Quality with a t-value calculated 2.953 with (sig 0.004<0.05) with df=106-3=103, then t table 1.659 is obtained.The results of the F test show that price and service quality together (simultaneously) have a positiveeffect on customer satisfaction of Lion Air Padang flight service users with the results of the F test knowing that the F value is calculated > from the F table or 20.683 > 3.08, with a significant value of 0.000 (p<0.05). From the results of the determinant coefficient analysis, an R-Square value of 0.287 was obtained, which means that 28.7% of the variables of price and quality of service can be explained by price and quality of service, while the remaining 71.3% is influenced by other factors outside the variables used in this study.